U.S. Interests in Central Asia Policy Priorities and Military Roles - Oliker, Olga (RAND Corporation, 2005)
The republics of Central Asia became more important to United States when U.S. forces were deployed there in support of Operation Enduring Freedom. The authors examine U.S. interests in the region, identify three main components of a successful military strategy there; and conclude that the U.S. military should have a relatively minor, but important, role in U.S. policy toward this part of the world.